Quality Testing of Purple Cabbage Extract (Brassica oleracea L. var capitata f. rubra) 70% Ethanol Fraction by Percolation Extraction Method - Praptanti Sinung Adi Nugroho; Ricka Prasdiantika (Indonesian Journal of Green Chemistry, 2026)
Multicomponent reactions are considered as the powerful tool in synthetic organic chemistry. They are efficient and one-pot reactions employing more than one starting materials leading to the formation of a final product. A wide range of heterocyclic compounds have been synthesized via multi-component reactions. In a mechanistically interesting MCR between amino triazoles, different carbonyl compounds and aromatic aldehydes, a mixture of isomeric heterocycles are obtained in good yields. Multicomponent reactions (MCRs) of H2S with different carbonyl compounds, amines and hydrazines have been carried out to get a variety of new types of sulphur and nitrogen containing heterocycles of immense medicinal importance. In a microwave assisted three-component reaction of 2,6-diaminopyrimidin-4-one, 4-hydroxycoumarin and aromatic aldehydes in DMF, Chromenopyridopyrimidines are formed in  excellent yields .However, addition of acetic acid to the same reaction mixture  leads to the formation of a different  compound. This article focuses on the recently proposed mechanisms for a series of multicomponent heterocyclization reactions. A wide range of advanced applications of the heterocycles synthesized via MCRs have also been discussed.